The Influence of Profitability, Company Size, and Profit Persistence on Earning Response Coefficient - Aisyah, Siti; Juardi (Summa : Journal of Accounting and Tax, 2023)
This study aims to determine the effect of Profitability, Firm Size, and Earnings Persistence on the Earning Response Coefficient. The sample used in this study is the consumer goods sector companies listed on the Indonesia Stock Exchange from 2017- 2021, with a total sample of 16 companies that meet the sample criteria determined through the purposive sampling method. The independent variables of this study are profitability as proxied by the ratio of Return on Assers, firm size as measured by Natural Logarithms, and earnings persistence as measured by using the regression coefficient between earnings in the current period and earnings in the period that has passed. The dependent variable of this study is the Earning Response Coefficient as measured by Abnormal Return and several other stages. The results showed that : (1) Profitability has no significant positive effect on earning response coefficient, (2) the size of the company has a negative and significant effect on earning response coefficient, (3) Earnings persistence has a negative and significant effect on earning response coefficient.